1989
DOI: 10.1346/ccmn.1989.0370405
|View full text |Cite
|
Sign up to set email alerts
|

Cation Migration in Smectite Minerals: Electron Spin Resonance of Exchanged Fe3+ Probes

Abstract: Abstract--The migration of interlayer Fe 3+ cations into the structure of heated montmorillonite and Laponite has been studied by electron spin resonance (ESR), MiSssbauer spectroscopy, and magnetic susceptibility measurements. The intensity of the ESR signal corresponding to interlayer Fe 3 § in air-dried montmorillonite and Laponite increased linearly as the amount of interlayer Fe 3 § increased. Changes in the spectra after thermal treatment indicate that Fe 3+ cations migrated into the pseudohexagonal cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Figure shows the XRD patterns of the samples Z-Na (a), Z-Fe (b), Z-FeAc (c), and Z-Femag1 (d). As can be seen, replacement of the sodium ions by the iron ions changes the d 001 parameter of the parent montmorillonite from 12.5 to 14.6 Å . After exposure of the Z-Fe sample to acetic acid vapors, there is an expansion of the interlayer region from 14.6 Å for the iron-saturated clay to 18 Å.…”
Section: Resultsmentioning
confidence: 93%
“…Figure shows the XRD patterns of the samples Z-Na (a), Z-Fe (b), Z-FeAc (c), and Z-Femag1 (d). As can be seen, replacement of the sodium ions by the iron ions changes the d 001 parameter of the parent montmorillonite from 12.5 to 14.6 Å . After exposure of the Z-Fe sample to acetic acid vapors, there is an expansion of the interlayer region from 14.6 Å for the iron-saturated clay to 18 Å.…”
Section: Resultsmentioning
confidence: 93%
“…Another prominent feature in Figure (B) is a broad peak approximately g = 2.2 found in one of the commercial ISP samples. A review of the literature indicates that this may be a form of hydrated surface iron (Coyne ; Luca and Cardile ). This peak at approximately g = 2.2 was greatly reduced after this same material was dehydrated with molecular sieves for 10 d (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Ben Hadj-Amara et al (1987) examined cation migration in Ni-exchanged beidellite using X-ray modeling techniques; their results suggested that Ni migrated into the vacant octa- hedral sites. Luca and Cardile (1989) studied the Fe(III) migration in smectites using electron spin resonance, M6ssbauer spectroscopy, and magnetic susceptibility measurements; no evidence for the penetration of Fe(III) into the vacant octahedral sites of montmorillonite was found. However, the penetration of Zn into the vacant octahedral sites of smectites is unlikely under field conditions where the temperatures and degree of desiccation are relatively low when compared with the conditions referred to above.…”
Section: Incubation Time (D)mentioning
confidence: 99%